Pengasuhan Anak Menurut Hukum Islam - Junaidy, Abdul Basith (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2017)
Divorce between husband and wife has consequences to child. Parental obligations to a child are not limited to the time of marriage, but continuing even if their marriage has been broken. The problem that arises is who between the two parents is more worthy of parenting. In principle, Islam provides provisions that mother is more worthy to nurture for a reason that mother is usually more loving than father. However, Islam as a religion with a rahmatan lil’alamin mision, sets a universal principle, namely the main requirement of a caregiver is to have an attitude of trust and ability. The term of trust (amanah) includes a good moral and not to damage the child's belief. Even, the non-Muslim caregiver is allowed as long as she is not concerned about damaging the child's belief. The term of “ability” requires a caregiver to spend time with the child. By this reason, the mother's position, for example, as a caregiver, can be replaced by a father if she is not trustful. Law on Marriage and Islamic Law Compilation (KHI) give strong emphasis on the trustworthy provision of a caregiver in the matter of maintenance and moral education to child. The Religious Courts is authorized to deprive the child’s custody of the untrust caregiver. In the matter of difference in religion, the Religious Courts is also authorized to decide whether it affects to the benefit of a child or not. [Perceraian yang terjadi antara suami isteri mengakibatkan konsekwensi terhadap pihak ketiga, yaitu anak-anak. Kewajiban orang tua terhadap anak tidak terbatas pada saat perkawinan masih utuh, akan tetapi kewajiban itu terus berlangsung meski perkawinan mereka telah putus. Persoalan yang muncul adalah mengenai siapa di antara kedua orang tua itu yang paling layak untuk melakukan pengasuhan. Secara prinsip, Islam memberikan ketentuan bahwa ibu lebih layak untuk mengasuh karena alasan biasanya ibu lebih memiliki kasih sayang dibanding ayah. Namun, Islam, sebagai ajaran yang memiliki misi Rahmatan lil Alamin, menetapkan prinsip universal dalam hal ini, yaitu syarat utama pengasuh anak adalah memiliki sikap amanah dan memiliki kecakapan. Syarat amanah meliputi  sikap moral yang baik dan tidak merusak agama anak. Pengasuh non muslim diperkenankan asalkan tidak dikhawatirkan merusak agama anak. Syarat kecakapan menuntut  kesediaan pengasuh untuk meluangkan waktu untuk anak.  Atas dasar itu, posisi ibu, misalnya,  sebagai pengasuh bisa saja digantikan ayah jika ia tidak amanah. Dan penentuan amanah atau tidaknya seorang pengasuh ditetapkan oleh Pengadilan Agama.]